Reliability of the Uchikomi Fitness Test: A Pilot study. Reliability of the Uchikomi Fitness Test - Almansba, R.; Sterkowicz, S.; Sterkowicz-Przybycien, K.; Comtois, A. S. (Science & Sports, 2012)
This study aimed to examine the reliability of an intermittent test simulating judo fight, the Uchikomi Fitness Test (UFT) (Almansba et al., 2007 [1]). Seven male judoists (20 ± 3 years) of different level of performance (four departmental, two regional and one national) effectuated that test during three sessions, each one separated by 48 hours. The results showed a modest reliability (ICC = 0.88) for average measure for the combined score (a + b) corresponding to the two best sets. However, the total number of uchikomi (n), responses of heart rate (HRmax, HRmean and %HRmax) showed a high reliability (ICC > 0.90) and a very low typical error of measurement (< 2%). This study showed that the measured variables were significantly reliable during three consecutive sessions. HRmax, HRmean and %HRmax are reliable indicators to assess the cardiovascular system of judoist. Additionally, the total number of uchikomi (n) obtained in UFT is a good indicator to provide relevant information about the physical fitness specific of judoist as it combines muscular solicitation and cardiovascular adaptation to effort.